Investigation of hybrid rocket motor regression rate doped with high entropy metallic additives - Ismail, Izham Izzat; Mohamad Jamil, Nur Arifah; Mohamad Anuar, Mai Nurul Fareesya; Azami, Muhammad Hanafi; Nordin, Norhuda Hidayah (American Institute of Aeronautics & Astronautics (AIAA), 2023)
Low combustion efficiency and low regression rate in the hybrid rocket limit the implementation of the Hybrid Rocket Motor (HRM) in the propulsion system. Due to this, a comprehensive investigation of utilising the paraffin wax doped with the high entropy metallic additives is used to enhance the regression rate, thrust, and specific impulse. Analytical studies are conducted to model the internal ballistic flow field in the combustion port at different initial configurations. The present investigation is focused on utilising aluminium, boron, magnesium, and High Entropy Alloy (HEA) energetic additives in the HRM. The percentages of energetic additives doped in the fuel are 10%, 20%, and 30% on a mass basis. HRM performance is also determined using various initial conditions such as initial mass flow rate, initial temperature, and initial pressure. The results demonstrate that aluminium has the highest regression rate among these four additives, followed by HEA, HEA with boron, magnesium, and boron. Furthermore, as the percentage of energetic additions increases, so does the rate of HRM regression rate. With a result of 17.50 mm/s, 30% of aluminium has the highest regression rate compared with others. Calculating thrust, Mach number characteristic velocity, and specific impulse has also been used to assess HRM performance. The findings show that increasing the mass flow rate has a significant impact on HRM performance. From the experimental results, it is found that adding High entropy alloy as energetic additives for solid fuel in hybrid rocket motor are proven to increase the regression rate up to 93.5% compared to using pure paraffin only. The experimental results validate the findings in simulation model.